Flow injection amperometric determination of persulfate in cosmetic products using a Prussian Blue film-modified electrode - De Oliveira, Marcelo F. [UNESP]; Saczk, Adelir A. [UNESP]; Gomes Neto, José Anchieta [UNESP]; Roldan, Paulo S. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (MDPI, 2003)
A flow-injection system with a glassy carbon disk electrode modified with Prussian Blue film is proposed for the determination of persulfate in commercial samples of hair bleaching boosters by amperometry. The detection was obtained by chronoamperometric technique and the sample is injected into the electrochemical cell in a wall jet configuration. Potassium chloride at concentration of 0.1 mol L-1 acted as sample carrier at a flow rate of 4.0 mL min-1 and supporting-electrolyte. For 0.025 V (vs. Ag/AgCl) applied voltage, the proposed system handles ca. 160 samples per hour (1.0 10-4 - 1.0 10-3 mol L-1 of persulfate), consuming about 200 μL sample and 11 mg KCl per determination. Typical linear correlations between electrocatalytic current and persulfate concentration was ca. 0.9998. The detection limit is 9.0 10-5 mol L-1 and the calculated amperometric sensibility 3.6 103 μA L mol -1. Relative standard deviation (n =12) of a 1.0 10-4 mol L-1 sample is about 2.2%. The method was applied to persulfate determination in commercial hair-bleaching samples and results are in agreement with those obtained by titrimetry at 95% confidence level and good recoveries (95 - 112%) of spiked samples were found. © 2003 by MDPI.
Keywords: Amperometry; Flow injection analysis; Persulfate; Prussian Blue film-modified electrode; Electrocatalytic effects; Prussian blue film-modified electrode; Catalysis; Concentration (process); Deposition; Electrochemistry; Graphite; Potassium compounds; Reaction kinetics; Volumetric analysis; Electrodes